CORRUPTION IN SOUTH AFRICA: GENESIS AND OUTLOOK - Georgieva Hadji Krsteski, Nataša (Journal of process management and new technologies, 2017)
Corruption in South Africa includes the private use of public resources, bribery and improper favouritism. South Africa scored 45 points out of 100 on the 2016 Corruption Perceptions Index reported by Transparency International. Corruption Index in South Africa averaged 46.97 Points from 1996 until 2016, reaching an all-time high of 56.80 Points in 1996 and a record low of 41 Points in 2011. A tenderpreneur is common corruption in South Africa. It is an individual who enriches themselves through corrupting the awarding of government tender contracts, mostly based on personal connections and corrupt relationships - although outright bribery might also take place - and sometimes involving an elected or politically appointed official (or his or her family members) holding simultaneous business interests. This is often accompanied by overcharging and shoddy workmanship. BEE-fronting is an abuse of the rules governing Black Economic Empowerment (BEE), where qualifying persons are given a seat on the Board of Directors of a company while having no decision-making power in the company, in order to qualify the company for government contracts in terms of BEE.